Mass spectrometry characterization of anticoagulant rodenticides and hydroxyl metabolites. (11th August 2020) - Fourel, Isabelle; Berlioz‐Barbier, Alexandra; Benoit, Etienne
Abstract : Rationale: Anticoagulant rodenticides (ARs) are used worldwide for rodent population control to protect human health and biodiversity, and to prevent agricultural and economic losses. Rodents may develop a metabolic resistance to ARs. In order to help understand such metabolic resistance, mass spectrometry was used to position the hydroxylated group of hydroxyl metabolites of second‐generation ARs (SGARs). Methods: Most AR pesticides are derived from the 4‐hydroxycoumarin/thiocoumarin family. We used low‐resolution and high‐resolution mass spectrometry to understand the fragmentation pathways of the ARs and their respective metabolites, and to better define the structure of their tandem mass spectrometry product ions. Results: Seven specific product ions were evidenced for five ARs, with their respective chemical structures. Those ions were obtained as well from the mass spectra of the hydroxyl metabolites of four SGARs, difenacoum (DFM), brodifacoum (BFM), difethialone (DFTL) and flocoumafen (FLO), with different positions of the hydroxyl group. Conclusions: The differences in chemical structure between DFM on the one hand and BFM, FLO and DFTL on the other could explain the differences in bioavailability between these two groups of molecules. The defined product ions will be used to investigate the part played by the metabolic issue in the field resistance of SGARs.